Factors That Influencing Informal Park and Ride Facility Choice in Indonesia: Case Study of Kendal Regency - Itrinna Fajar; Achmad Djunaedi (Universitas Batanghari Jambi, 2020)
Park and Ride offers an efficient alternative to accessing major transport nodes in low-density settings. In Kendal Regency these facilities allow people to choose between drive and ride bus when they arrive in national road.A stated preference survey was carried out to get insight how to improve utilization of local P&R. Binary logit model is applied since the alternative of parking facility choice is limited into two categories peripheral P&R facilities and local P&R facilities. Based on stated preference survey processed by R statistics, the result of type of P&R facility choice under hypothetical scenarios as follow: (1) variables that significantly affect park and ride choice behavior are gender, cost, amenity, overnight service and type of spatial use. Whereas factor age and capacity do not significantly affect park and ride type choice. (2) Even though variable cost is significant, but the variable is insensitive to P&R type choice. While variable number of amenity is more sensitive to P&R type choice.